Finance and development in Africa - Menjah, Kojo; Abor, Joshua (Research in accounting in emerging economies ;, 2012)
The objective of "Research in Accounting in Emerging Economies" is to raise the level of interest in the specific problems of accounting in emerging economies; and increase awareness of real issues, so that accounting in these countries will not just be seen as a matter of copying what is done in the industrialized countries. "RAEE" is intended to provide an authoritative overview of accounting research and progress in emerging economies.